Effect of inherited structural highs on the structure and kinematics of the South Dezful Embayment, SW Iran - Shamszadeh, Aref; Sarkarinejad, Khalil; Ferrer, Oriol; Mukherjee, Soumyajit; Seraj, Mohammad (Geological magazine, 2022)
Understanding the structural evolution of the South Dezful Embayment (SDE) in the Zagros Fold-and-Thrust Belt (ZFTB) is significant for hydrocarbon exploration and production. The structural evolution of this area has been controlled by the reactivation of basement structures related to the oblique convergence along the ZFTB. In this work, we study the effect of the pre-contractional interaction between the basement step and overlaid salt layer superimposed by the Zagros shortening on the structural style and evolution of the sedimentary basin in the SDE. We use multidisciplinary approaches involving surface and subsurface data and analogue models. Disharmonic folds with small wavelength formed over the Kharg-Mish Palaeo-high (KMPH) where the sedimentary cover is thinner. On the other hand, faulted detachment folds with large wavelengths developed in the adjacent depocenters. Furthermore, the KMPH affected the geometry and kinematics of the frontal part of the Zagros Belt, which is characterized by the Mountain Front Flexure (MFF) topographic step. Long-lasting active deformation of the sedimentary cover over the frontal ramp of the KMPH developed the South Izeh Promontory (SIP). Localized contraction in the SIP was accommodated temporally by trishear fault-propagation folding and resulted in > 5 km elevation difference between this promontory and two adjacent local basins. Supporting scaled analogue models show that structural evolution, folding and along-strike variations in fold style of the SDE have been controlled by thickness variations of the sedimentary cover and the geometry of the inherited pre-salt structure. Based on the results of this study, the effect of inherited structural highs on the structure and kinematics of the SDE provide important insights for hydrocarbon entrapment, migration and exploration.